2017
DOI: 10.1016/j.amjmed.2017.04.043
|View full text |Cite
|
Sign up to set email alerts
|

A Deficiency of Nutrition Education and Practice in Cardiology

Abstract: A large proportion of cardiovascular specialists have received minimal medical education and training in nutrition, and current trainees continue to experience significant education and training gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 15 publications
1
64
0
Order By: Relevance
“…As a consequence, physicians often lack the necessary knowledge, skills and confidence to counsel their patients effectively 6. For example, a survey among cardiologists showed that 90% reported that they did not receive adequate nutrition education during fellowship, even though 95% believed that their role includes providing patients with at least basic nutrition information 7…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, physicians often lack the necessary knowledge, skills and confidence to counsel their patients effectively 6. For example, a survey among cardiologists showed that 90% reported that they did not receive adequate nutrition education during fellowship, even though 95% believed that their role includes providing patients with at least basic nutrition information 7…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey of North American cardiologists, 90% reported receiving no or minimal nutrition education during fellowship training, 59% reported no nutrition education during internal medicine training and 31% reported receiving no nutrition education in medical school [62]. Consider the specialty of early-life care where multi-generational health is on the line-pediatrics.…”
Section: Lifestyle In Training and Practicementioning
confidence: 99%
“…Generally, information about the benefits of nutritional interventions has not adequately been translated into action in medical training or practice [2]. In a 2017 online survey of 646 cardiologists in the US [3], 90% reported that they had not received adequate nutrition education to be able to counsel their patients, even though 95% believed it was their personal responsibility to do so.…”
Section: Introductionmentioning
confidence: 99%